Broken chest tube: a rare complication treated by video-assisted thoracic surgery - Bakhshi, Girish D.; Rahul, Kushagra; Gangawane, Shraddha S.; Borade, Ashwini S.; Pawar, Dinesh S.; Parikh, Atish K. (International Surgery Journal, 2019)
Intercostal chest drain (ICD) or chest tube is a simple device used very frequently in medical, surgical and critical care specialties to drain air, blood or pus from the pleural cavity. Fracture of ICD and displacement of fractured segment within the pleural cavity is a rare complication. Minimal invasive approaches via video-assisted thoracic surgery (VATS) have been demonstrated predominantly in traumatic thoracic foreign body removal cases in a primary surgical setting. Here we present a case of a broken chest tube in the pleural cavity removed using VATS. A brief case report, review of literature and prevention of this complication is described.